Sensory neuron LKB1 mediates ovarian and reproductive function - Melissa E Lenert; Emily K Debner; Michael D Burton (Scientific Reports)
Abstract Treatments for reproductive disorders in women consist of hormone replacement therapy, which have negative side effects that impact health, spurring the need to understand new mechanisms to employ new therapeutic strategies. Bidirectional communication between sensory neurons and the organs they innervate is an emerging area of interest in tissue physiology with a relevance in reproductive disorders. We hypothesized that the metabolic activity of sensory neurons has a profound effect on reproductive phenotypes. To investigate this phenomenon, we utilized a murine model with conditional deletion of liver kinase B1 (LKB1), a serine/threonine kinase that regulates cellular metabolism in sensory neurons (Nav1.8cre; LKB1fl/fl). LKB1 deletion in sensory neurons resulted in reduced ovarian innervation from dorsal root ganglia neurons and increased follicular turnover compared to littermate controls. Female mice with this LKB1 deletion had significantly more pups per litter compared to wild-type females. Interestingly, the LKB1 genotype of male breeders had no effect on fertility outcomes, thus indicating a female-specific role of sensory neuron metabolism in fertility. In summary, LKB1 expression in peripheral sensory neurons plays an important role in modulating fertility of female mice via ovarian sensory innervation.